Craniofacial photography for detection of positional obstructive sleep apnoea - Kate Sutherland; John Wheatley; Kristina Kairaitis; Brendon J. Yee; Gary Cohen; Kerri Melehan; Stephen Lambert; Philip de Chazal; Peter A. Cistulli; Peter Cistulli; Philip de Chazal; Nina Sarkissian; et al. (Sleep and Biological Rhythms, 2026)
Supine-dependent OSA is a well-recognised OSA phenotype and may relate to craniofacial structure. Our aim was to assess whether craniofacial photos are able to identify positional OSA, specifically supine-isolated OSA, in comparison to non-positional OSA. Frontal and profile craniofacial photographs of participants were acquired according to a standardised protocol. Photographs were analysed and compared between non-positional and supine-isolated OSA groups. A total of 156 OSA patients were included (54.5% supine-isolated OSA, 45.5% with non-positional OSA). The supine-isolated group had a longer upper face height and greater upper-to-lower face height ratio, smaller face width, reduced face width-to-height ratio, and smaller mandibular width, length, and size of the mandibular base. Differences in facial measurements were no longer significant after adjustment for body size and OSA severity. Our study demonstrates that supine-isolated OSA can be identified using facial photography. Larger studies in groups matched for BMI and OSA severity are needed to confirm whether this technique may also capture other features related to supine-isolated OSA (i.e., differences in underlying skeletal structure).